Patient’s expectations and perceptions on quality of care; An evaluation using SERVQUAL gap in Kenya - Agnes Karingo Karume; Kelvin Nyongesa; Lydia Okutoyi; John Kinuthia (PLoS ONE, 2025)
Background Assessing healthcare quality is pivotal for patient-centric enhancements. Employing the Gaps Model of Service Quality and SERVQUAL, this study determined patient expectations and perceptions of care quality at a national referral hospital. Methods In this cross-sectional study, data were gathered pre and post care using a semi-structured tool with 380 participants. Statistical package for social sciences(Version 25) facilitated analysis. Quality indices, expressed as percentages of weighted averages, compared expected and perceived care. Service quality gaps, which represented the difference between perception and expectation (P – E), were assessed via paired-sample t-tests. Logistic regression were used to examine factors linked to positive service quality gaps. Results Median age was 34 years, 74% were female, 57% had non-formal employment, and 49% had attained secondary education. The gap index across all components was -10%. The largest gaps existed in SERVQUAL’s reliability and empathy domains. Secondary education (OR = 2.13, 95% CI: 1.01–5.21,p = 0.003; aOR =  2.0, 95%CI: 1.57–7.11) and non-formal employment (OR = 1.54, 95% CI: 1.01–4.11, p = 0.01; aOR =  1.40, 95%CI: 1.08–5.12) correlated with positive health service quality gaps. Conclusions Patient expectations exceeded perceptions of care quality, emphasizing the need to align service delivery and actively manage patient expectations, particularly in areas of reliability and empathy, such as timeliness and compassion.